Analysis of Learning Behavior, Persistence, and Conceptual Understanding of Students with Hearing Impairments in Visual Learning at Manunggal Special School, Slawi (Jurnal Wahana Konseling, 2026)
This study aimed to analyze the learning behavior, persistence, and conceptual understanding of Grade VI students with hearing impairments in visual learning at Manunggal Special School, Slawi. A descriptive qualitative design with a case study orientation was employed. Participants consisted of one classroom teacher and six students with hearing impairments selected purposively. Data were collected through classroom observation, visual worksheet analysis, field notes, and teacher confirmation. The observation focused on learning focus, visual response, conceptual understanding, independence, and persistence, using a four-point scoring scale. The findings showed that students obtained high scores ranging from 3 to 4 across most observed indicators, indicating good to very good engagement. Visual learning supported students’ ability to follow instructions, recognize images, match pictures with concepts, complete simple arithmetic tasks, and persist in completing worksheets despite communication barriers. The teacher’s use of pictures, demonstrations, sign language, facial expressions, and concrete examples helped transform verbal concepts into accessible visual information. The study concludes that visual learning functions as pedagogical accessibility for students with hearing impairments. It supports not only conceptual understanding but also learning persistence and independence. These findings highlight the importance of structured visual media and empathetic teacher communication in special education classrooms more meaningfully.